(untitled) (Revista do Centro de Estudos Portugueses, 2000)
Este ensaio estuda a ideologia do dandismo, originário da Inglaterra no século XIX, para focalizar, em Jacinto de Tormes, protagonista do romance A cidade e as serras, de Eça de Queiroz, as manifestações de superposição e semelhança – origem, aparência, comportamento político e social – com as do dândi baudelairiano. O trabalho demonstra que Jacinto apresenta uma identidade indubitavelmente portuguesa, e que não pode ser visto como um mero estereótipo do fenômeno em questão. This essay studies the ideology of dandyism – which emerges in the 19th century England – in order to analyze Jacinto de Tormes, the protagonist of A cidade e as serras by Eça de Queiroz. The analysis focuses on the manifestations of superposition and similarity of origin, appearance, political and social behavior revealed in Eça’s character and in the baudelairian dandy. The conclusion demonstrates that Jacinto presents an undoubted Portuguese identity, and that he cannot be seen as a mere stereotype of the dandy.